Socialization and training on production of bio-charcoal made from biomass waste using a double-tube reactor - Lukas Kano Mangalla; Raden Rinova Sisworo; Budiman Sudia; Samhuddin Samhuddin; Minson Simatupang (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Proper handling of biomass waste can turn waste into something beneficial for society. One way that can be done is to convert biomass waste into quality biochar for energy needs and agriculture as a planting medium. This partnership program is intended to provide education and practical knowledge to the community regarding utilizing biomass waste for biochar production using a double tube reactor. The activities consisted of socialization of the impact of the abandonment of biomass and the benefits of biomass for household energy needs, as well as practical experience of carbonizing biomass by directly involving partner communities. This activity was carried out at Pambulaan Jaya Village Hall attended by 32 community partners and 9 teams from Halu Oleo University. This partnership activity is very relevant for people in the village where most of the population lives as rice and field farmers. The practical knowledge on carbonizing biomass waste was conducted in two days for the two types of biomasses, namely wood chips and coconut shells. The community was very enthusiastic about continuing the carbonization process after they learned about the great benefits of this biochar product for household energy needs, growing media for plantations, and increasing their income.